Monotonicity of Topological Entropy for One-Parameter Families of Unimodal Mappings - Volkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For a special class of one-parameter families of unimodal mappings of the form f t(x): [0, 1] → [0, 1], f t = atx/(x + t), 0 ≤ x ≤ 1/2, we establish that, for t ε [0, 1/(a − 2)], a > 2, the topological entropy h(f t) is a function monotonically increasing in the parameter. We prove that there exists a class of one-parameter families of unimodal mappings f t that contains the family indicated above and establish conditions under which the topological entropy h(f t) is a function monotonically increasing in the parameter.